Multimodality treatment on gastric cancer with liver metastasis: case report - Li, Mengnan; Wang, Gongchen; Chen, Lianyu; Zhuang, Liping; Chen, Hao (Frontiers in Oncology, 2025)
BackgroundAdvanced gastric cancer has a devastating prognosis, However, the optimal treatment for gastric cancer patients with multiple liver metastases(GCLM) remains yet to be fully elucidated. Cryoablation is a novel therapeutic approach that has the potential to induce tumor necrosis and elicit anti-tumor immune responses.Case presentationA 44-year-old male was diagnosed with advanced gastric adenocarcinoma. Despite undergoing multiple lines of systemic therapy and repeated locoregional treatments, the patient exhibited rapid tumor progression. Subsequent treatment with PD-1 inhibitors demonstrated limited efficacy. However, following the innovative application of cryoablation to eradicate a more significant lesion within the liver metastases, the patient achieved a partial response and experienced 15 months of progression-free survival (PFS) with the combined use of PD-1 inhibitors and chemotherapy at the time of this report.ConclusionCryoablation combined with immunotherapy may provide potential benefits for specific patients and offer a meaningful therapeutic strategy for patients with advanced gastric cancer and liver metastases, which is worthy of further research.